Magnesium sulphate is it necessary to prevent eclampsia? - Jaybhaye, Deepali Laxman; Chaudhary, Prashant; Gite, Amol; Kaur, Shkhmin; Kadam, Rajesh (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Preeclampsia was reported to account for 15 % of all antenatal hospitalization for pregnancy complications. It causes maternal as well as fetal death by developing eclampsia Since the turn of the century, obstetrician have to decrease the incidence of eclampsia i.e hypertension complicated with seizures in pregnant women by treating them magnesium sulfate in preeclampsia. In our study we tried to find out Magnesium sulphate really helpful in prevention of eclampsia or not. Methods: This prospective study was carried out by the department of Pharmacology with the help from department of obstetrics and gynecology, in rural hospital and medical college i.e Mahatma Gandhi Institute of Medical sciences Sewagram, Wardha, Maharashtra, India during January 2007 to January 2008. A total of 100 subjects registered in inpatient department were included in this study. Patients were divided in to two group one group receiving nifedipine (calcium channel blockers) and other group receive combination of nifedipine and magnesium sulfate. We compared the delivery outcome of both the group. Results: Patients receiving nifedipine had good pregnancy outcome with less side effects than the patients receiving combination of nifedipine and magnesium sulphate. Conclusions: Magnesium sulphate is not necessary drug for prophylaxis of eclampsia.